STABILITY OF ADDITIVE - QUADRATIC MAPPINGS IN BANACH SPACE NON-ARCHIMEDEAN - Cruz Huallpara, Alex Armando (2013)
In this paper we study the generalized Hyers-Ulam stability of the quadratic-additive functional equation in a Non-Archimedean Banach space, using the direct method and the fixed point.